Nose-to-brain delivery of microcarrier in the treatment of neurodegenerative diseases - Saurav Pandey, Nidhi Nainwal, Teena Negi, Amit Kumar Lohar, Saurabh Kumar, Shubhankar Kumar, Amrita Bisht (Journal of Applied Pharmaceutical Science, 2025)
Neurodegenerative diseases (NDs) have emerged as a major global health concern due to the perpetually aging population and unhealthy lifestyle. The most prevalent NDs, such as Alzheimer’s, Parkinson’s, and Migraine, have seen a great deal of research into dependable and efficient treatment approaches. However, the conventional approach to treating NDs is not very effective due to the presence of the blood–brain barrier (BBB). BBB is a major hurdle for the delivery of various therapeutic agents to the brain. Nasal drug delivery is a novel approach providing direct delivery of drugs to the brain through the olfactory and trigeminal neurons. The nasal route also guarantees quick absorption, avoiding first-pass metabolism and early action of therapeutic activity. The nasal cavity has excellent permeability and effective absorption, of drugs including peptides, proteins, and tiny molecular weight polar medicines, which are difficult to administer by anything other than injection or where a fast onset of action is necessary. Microspheres (MSs) are micron-sized particles that can be used in nose-to-brain delivery. The main justification for using MSs for nose-to-brain delivery is to increase the likelihood that the medication will be absorbed by enabling closer and longer contact between the medication and the mucosal barrier. MSs swell on contact with nasal mucosa and solidify into a gel to prevent its clearance from the nasal cavity. This article made a comprehensive review of the application of MS in nose-to-brain drug delivery as a unique approach to treating NDs.
Keywords: Neurodegenerative diseases, microcarriers, application, blood–brain barrier, intranasal route